2010
DOI: 10.4314/sajas.v39i4.51130
|View full text |Cite
|
Sign up to set email alerts
|

Mortality determination and gender identification of conceptuses in pregnancies of Santa Ines ovine by ultrasound

Abstract: The aim of this study was to monitor early gestation in Santa Ines ewes by ultrasound in order to determine embryo and foetal loss, and to identify foetal sex. Ewes (n = 132) were submitted to controlled natural mating. For the purpose of pregnancy diagnosis and embryo monitoring we used transrectal ultrasound with a linear transducer (6.0 and 8.0 MHz). Pregnancy was diagnosed on day 30. On day 35 ultrasound examination was performed to determine embryo viability or loss. On days 40, 50 and 60 ultrasound exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
1
5
0
1
Order By: Relevance
“…13 present study during the embryonic period compared with those occurred during the fetal period was 318 consistent with those reported in other studies in sheep [7, 8,15], and cattle [17,18]. For examples, in 319 sheep, Moraes et al [8] observed a higher embryonic loss of 10 % between D30-40 and fetal loss 320 percentage of 4.4% between D40-60.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 94%
See 2 more Smart Citations
“…13 present study during the embryonic period compared with those occurred during the fetal period was 318 consistent with those reported in other studies in sheep [7, 8,15], and cattle [17,18]. For examples, in 319 sheep, Moraes et al [8] observed a higher embryonic loss of 10 % between D30-40 and fetal loss 320 percentage of 4.4% between D40-60.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 94%
“…For examples, in 319 sheep, Moraes et al [8] observed a higher embryonic loss of 10 % between D30-40 and fetal loss 320 percentage of 4.4% between D40-60. Recently, it was found that the late embryonic death rate 321 between days 20 and 40 was substantially higher (p<0.05) than the fetal mortality rate in sheep [15].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Indications of ovine embryonic death were observed via ultrasonography by Barbagianni et al [25] when there was shrinkage of the embryo, absence of fetal heartbeat and movements later followed by a lack of anechoic fluids, and disappearance of previously observed placentomes. Moraes et al [26] found 10% embryonic loss from among the 160 Santa Ines ewes studied using ultrasonographic analysis. Also noteworthy is that the mortality rates were significantly lower in single pregnancies as compared to multiple pregnancies.…”
Section: Methods For Assessment Of Embryonic Mortalitymentioning
confidence: 97%
“…Economic losses resulting from fetal death are substantial since they include not only the loss of offspring but also a prolonged open period for the dam leading to increased culling rates [4]. The high rate of embryonic loss (25–40%) in domestic species during early pregnancy may result in false positive diagnosis [6]. The causes of fetal death are multifactorial and can be divided broadly into infectious and non-infectious origin with the most frequently detected infectious agents being bacteria, viruses, fungi, and parasites.…”
Section: Introductionmentioning
confidence: 99%